Comparison Between Clinical Observation and ChatGPT-Assisted Dental Assessment in School Children - Moin Khan, Meher; Khan, Oneeb; Wasay Jeelani, Muhammad; Yousaf, Shoaib; Farrukh, Raima; Ajmal, Jannatain (Journal of Neonatal Surgery, 2025)
This observational cross-sectional comparative study was conducted at the Department of Community and Preventive Dentistry, Watim Dental College and Hospital, Rawalpindi, between March 2025 and September 2025, to compare the accuracy and consistency of clinical dental examinations with ChatGPT-assisted assessment in evaluating dental caries and oral hygiene among school children. Clinical oral examinations were performed on children aged 5–10 years using standard WHO oral health criteria, and the same intraoral images were analyzed using ChatGPT for caries detection and oral hygiene evaluation. The findings were compared for agreement using descriptive statistical methods. The AI-based assessment demonstrated an 87.5% agreement rate with clinical diagnosis for caries detection and 90% for oral hygiene evaluation, with minor discrepancies observed in borderline caries cases. The study concludes that ChatGPT shows promising accuracy in identifying dental caries and assessing oral hygiene, closely aligning with clinical observations, and has the potential to serve as a supportive tool in large-scale oral health screening and preventive dental programs..